Interlinked chemical-biological processes in anoxic waterlogged soil – A review - BHADURI, DEBARATI; MANDAL, ASIT; CHAKRABORTY, KOUSHIK; CHATTERJEE, DIBYENDU; DEY, RINKU (The Indian Journal of Agricultural Sciences, 2017)
Wetland soils are predominantly oxygen-free includes swamps, marshes, coastal wetlands, floodplains, etc. and globally important for rice cultivation. The chemical changes happen due to changing electrochemical properties and also by anaerobic microorganisms. Anaerobic microorganisms play a key role in bringing about nutrient transformations with a general trend of increase in soil pH, electrical conductivity, and ionic strength but decrease in redox potential in waterlogged soils. The biogeochemical cycling of nutrients (C, N, P, S) by facultative and obligate anaerobes help to sustain life in submerged conditions. Under flooded conditions the availability of P, Ca, Mg, Fe, Mn, Mo, and Si increases while that of S, Zn and Cu decreases. Moreover, fermentative bacteria decompose organic matter into CO2, H2, acetate, propionate, butyrate, fatty acids, amino acids, alcohols, etc. with a terminal step of methane formation by methanogens. Anaerobic soils are thus important for maintaining fertility, ecosystem productivity, and functions.